Pengaruh industri mebel terhadap pola tata letak ruang rumah usaha di Desa Jorongan, Probolinggo - Adita Ronarizkia; Lisa Dwi Wulandari; Yusfan Adeputera Yusran (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Jorongan Village is as an area designated as the Furniture Industry Center of Probolingggo Regency, thereby leading to changes in some houses functionality from residential to business. This certainly changes the internal and external layout of the houses used for furniture business. The purpose of this research is to identify the spatial layout pattern of business houses in the furniture industrial center area of Probolinggo Regency. This research was carried out with the behavior mapping approach used to describe the existing space in each furniture business house. Therefore, based on the analysis results, there are four patterns of business function space layout, the first, second, and third are located at the front, side and partially inside the building, while the other part is located in the side. Furthermore, the pattern with part of the business function space is located inside the building, and partly outside the front and side of the house. The result showed that three houses had irregular patterns with different layouts from other businesses.